Validasi Metode Analisis Rebamipid Dalam Plasma In Vitro Secara Kromatografi Cair Kinerja Tinggi-Ultraviolet - Harahap, Yahdiana; Alia, Nu (Majalah Ilmu Kefarmasian, 2009)
Rebamipide is antiulcer agent and it is one of the drug that have to be evaluated with bioequivalency test according to Food and Drug Administration (FDA). The objec-tive of this research is to find out the optimum condition of rebamipide in human plasma in vitro analysis by High Performance Liquid Chromatography (HPLC) with ultraviolet detector, and then the method was validated. The chromatography was carried out by isocratic technique on a reversed-phase Kromasil® C18 (5 µm, Akzo Nobel), column length was 250 x 4.6 mm, with mobile phase consisted of acetonitrile - phosphate buffer pH 3.0 (40:60) at flow rate of 1.0 ml/min, and detection was performed at wavelength of 230 nm. The sample preparation technique was liquid-liquid extraction by phosphoric acid and ethyl acetate. Carbamazepine was used as the internal standard. The method was valid according to FDA in Bioanalitycal Method Validation, with coefficient correlation of 0.9993 and linear in the range concentra-tion of 0.04 – 1.2 µg/ml, the lower limit of quantitation was 42.0 ng/ml, precision less than 6% and recovery percentage was 90.32 to 113.45%. Rebamipide in plasma was stable for 14 days storage in -200C.